Phytochemical Screening and Immunomodulator Activity of Mimusops elengi Linn. - Singh, Nandlal; Irchhaiya, Raghuveer; Gupta, Rishikesh; Prajapati, Ram Narayan; Dixit, Vihangesh (Journal of Drug Delivery and Therapeutics, 2019)
Aim.  Phytochemical screening screening and investigation for immunomodulatory activity of ethanolic extract of leaves of Mimusops elengi using different parameters like carbon clearance, albumin globulin ratio, delayed type hypersensitivity reaction, total leukocyte count and estimation of immunoglobulin etc.Material and Methods. Ethanolic extract  of the plant leaves was  prepared. Preliminary phytochemical screening has been conducted. 1g of carragenan was dissolved in 100ml. of water for injection. 1% w/v suspension of carbon black as Indian ink. 2% PVP solution is prepared in water for injection. Four sets (A,B,C and D) of the animals were taken. Each set contains five groups and each group has six animals. After that different parameters of imunomodulation were performed.Result and Discussion. Phagocytic index was determined by measuring the concentration of Indian ink at different time intervals. The rate of Carbon clearance is a measure of Phagocytic activity, The result ( table 2 and  and fig 1) Suggested that in the case of control animals, the concentration of Indian ink obtained after 12 minuts of experimental time was decreased nearly 52% of its initial value as compared with the value recorded initially at 3 minuts. this decreased could be described of the natural course of phagocytosis to the particles by liver macrophages. on the other hand the ethanolic extract of the mimusops elengi  showed Significant immunostimulant activity as reflected by lower recovery of carbon particles as compared against that obtained by the control. the same trend was followed even after increasing the dose and the result were found to be directly influence by the increase in dose.Conclusion. The results of this study clearly indicate that the Ethanolic extract of M. elengi linn.leaves can be used as promising immunostimulating agents. The activity may be due to the presence of phytochemicals reported through phytochemical screening.Keywords:  Mimusops elengi, solvent extraction, carbon black as Indian ink.